IMPROVING METHODS FOR DIAGNOSING AND MONITORING ENDOTOXICOSIS IN EXPERIMENTAL DIAETIC FOOT SYNDROME - Ergashev U.Y.; ErnazarovKh.I.; Zohirov A.R.; Minavarkhojayev R.R.; Mominov A.T. (Scholar Express Journals, 2023)
The aim of the study was to compare the effect of the new drug "Rheomannisol" on physiological parameters in the treatment of experimental diabetic foot syndrome.
Keywords: experimental model of diabetic foot; experimental animals; diabetes mellitu